Cultivating Independent Attitudes in Early Childhood Through Project Based Learning - Devika Fatma Hidayat; Tsani Koirunnisa; Galuh Putri Jasmine (Penerbit Hellow Pustaka, 2024)
Independence is a condition where a person is able to stand alone without depending on others. Instilling an independent attitude in early childhood can be done using project-based learning methods. Project-based learning is learning that uses projects or activities as media. This research uses a literature review with data collection sources coming from journal articles, internet articles, books, papers and other sources of information that are in line with the research topic. The aim of this research is to explore information about the effectiveness of project-based learning on children's independent attitudes. The research results show that project-based learning can be an effective strategy in developing independence in young children.